EFEKTIVITAS MODEL TWO STAY TWO STRAY (TSTS) TERHADAP PEMBELAJARAN KETERAMPILAN BERBICARA SISWA KELAS VII SMP NEGERI 1 SUNGGUMINASA (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
This study aims to describe the conventional learning model in the control class in determining speaking ability, cooperative learning type Two Stay Two Stray in the experimental class in determining speaking ability, and the effectiveness of the use of cooperative learning model type Two Stay Two Stray in determining speaking ability during Indonesian language learning for VII grade students of SMP Negeri 1 Sungguminasa. The approach used in this research is descriptive quantitative approach, the data source is Indonesian language teacher in SMP 1 Sungguminasa. The form of data in this study is the skill of providing reinforcement by Indonesian language teachers. The data collection technique in this research is oral technique. The results showed that the conventional learning model in the control class was in the less category with an average value of 57.65% which means that students are less able to stimulate students' speaking activeness. Furthermore, the Two Stay Two Stray cooperative learning model in the experimental class is in the good category with an average value of 86.94% which means that students are able to improve their speaking skills well. Then, the cooperative learning model of Two Stay Two Stray Type is effectively used in learning students' speaking skills compared to the conventional learning model.